Risk Management Strategies in Facing Global Financial Market Volatility - Darwin Nasution (Involvement International Journal of Business, 2024)
Global financial market volatility refers to the unpredictable fluctuations in the prices of financial assets such as stocks, bonds, currencies, and commodities. This volatility can stem from various factors such as economic indicators, geopolitical events, policy changes, technological advancements, and investor sentiment. This research aims to analyze effective risk management strategies in facing global financial market volatility. Market volatility often triggers anxiety, uncertainty, and irrational investment decisions. In this situation, it is important for investors to adopt the right strategies to minimize risks and maximize long-term investment outcomes. In this study, data is collected from various sources related to global financial market volatility and risk management strategies adopted by investors during periods of uncertainty. Qualitative and quantitative analyses of this data are conducted to identify patterns of investor behavior and the effectiveness of applied risk management strategies. The research findings indicate that maintaining a long-term perspective, retaining portfolio diversification, and taking an active approach to risk management are effective strategies in dealing with market volatility. Open communication with financial professionals is also proven to be essential in helping investors stay calm and make rational decisions.